Seroprevalence and associated risk factors of hepatitis C infection among diabetic patients in South‐Kivu, Eastern Democratic Republic of the Congo: A cross‐sectional study - Yannick Chibinda Birato; Tony Akilimali Shindano; Daudi Cinyabuuma; Ciza Abel; Cikomola Justin Chiruza; Andre N. H. Bulabula (Health Science Reports, 2023)
Abstract Background and Aims Hepatitis C virus (HCV) infection and diabetes mellitus (DM) are two frequent diseases in the Democratic Republic of the Congo (DRC) and several studies seem to show a link between the two diseases worldwide. However, no study has evaluated this link in our country. The present study aimed at determining the seroprevalence of HCV in diabetic patients as well as associated risk factors. Methodology A multicenter cross‐sectional study allowed us to sample diabetic patients in two diabetic healthcare centers of Bukavu city in the eastern part of the DRC, from December 2020 to December 2022. A questionnaire was submitted to the diabetic patients to collect sociodemographic data, anamnestic data on risk factors for HCV infection, and clinical data on DM. These factors were analyzed based on anti‐HCV serological results. Results Among the 180 selected patients, 19 (10.6%) were tested positive for anti‐HCV antibodies. After multivariate analysis, the identified factors influencing these outcomes were male sex (adjusted odds ratio [aOR]: 3.5, p = 0.027), dental extraction (aOR: 7.6, p = 0.001), and living in a privileged environment (aOR: 0.29, p = 0.03). The factors related to DM such as the type, the disease duration, or the usual type of treatment did not influence the serological results. Conclusion This study shows that HCV seroprevalence in diabetic patients is very high compared with the general population. This suggests combined screening and management policies in this population.